Manajemen Sarana Prasarana Pendidikan Dalam Menunjang Mutu Pendidikan Di SD IT Al-Amin Sindangkasih Ciamis - Mohamad Thibyan; Yat Rospia Brata; Tatang Parjaman (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
Educational facilities are an important factor that must be a concern for anyone working in the world of education. In general, educational facilities include all facilities that are directly related to teaching and learning activities, for example: buildings, study rooms or classrooms, teaching aids or equipment, tables, chairs, etc. Meanwhile, infrastructure is what indirectly supports learning. Basically, educational facilities can be classified into four types, namely land, buildings, school equipment and furniture (site, building, equipment and furniture). In order for all these facilities to make a significant contribution to learning, they must be managed well. This management is better known as management, and the management in question consists of: (1) Planning, (2) Procurement, (3) Arrangement, (4) Use, (5) Supervision. In general, infrastructure is an aspect that supports the success of the work process. in service, because if these two things are not present then all the actions carried out will not be optimal as planned.